2014
DOI: 10.3944/aott.2014.2985
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell application improves tendon healing via anti-apoptotic effect (Animal study)

Abstract: The application of MSCs to decrease re-ruptures has a positive effect on tendon strength, probably due to their anti-apoptotic effects. Mesenchymal stem cell application can be used percutaneously and is effective in clinical practice in the late stages of tendon healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…At the 12th week, apoptosis was minimally present in the study group and was clearly increased in the control group. Increase in tendon strength was signifi cantly higher in the study group than in the control [ 45 ].…”
Section: Different Treatment Modalities In Tendon Healingmentioning
confidence: 85%
“…At the 12th week, apoptosis was minimally present in the study group and was clearly increased in the control group. Increase in tendon strength was signifi cantly higher in the study group than in the control [ 45 ].…”
Section: Different Treatment Modalities In Tendon Healingmentioning
confidence: 85%
“…In many studies on animals, MSC administration has been shown to accelerate Achilles tendon recovery and have positive effects (14,15). Studies have shown that it increases tendon strength significantly and that good histopathologic scores have been obtained, but its mechanism of action has not been fully explained yet (16). The effects of MSCs not only involve transdifferentiating into other cells, but also causes the release of paracrine cells, such as growth factors and cytokines (17).…”
Section: Introductionmentioning
confidence: 97%
“…After 12 weeks the strength of tendons was significantly improved. Immunohistochemical evaluation showed increased localization of MSCs in the area of the repair zone [53]. Bone marrow derived MSCs have been shown to improve the mechanical properties of rabbits' patellar tendons [6].…”
Section: Healing Of the Tendonmentioning
confidence: 99%
“…Animal models showed positive results of MSCs application in tendon repair process. Authors obtained MSCs from femurs and tibias of rats and injected to the ruptured Achilles tendon [53]. After 12 weeks the strength of tendons was significantly improved.…”
Section: Healing Of the Tendonmentioning
confidence: 99%